Green Accounting On The Financial Performance Of Pt. Sari Coffe Indonesia - Dyah Ayu Pramesti; Novia Paramida; Maria Yovita R.Pandin (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The activities of a company will have an impact on the environment. The application of green accounting in companies can improve the company's environmental performance which ends in an increase in financial performance with environmental benefits that can be managed and preserved properly according to government regulations. This study aims to analyze the application of green accounting by companies and determine the effect of green accounting on the company's financial performance.